Pelatihan Optimalisasi Solar Cell Sebagai Sarana Penerangan Mitra : Karang Taruna di Pulau Pari - Oktarina Heriyani; Dan Mugisidi; Riyan Ariyansah; Lutfan Zulwaqar; Mujirudin Mujirudin (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The optimization training for solar cells as a lighting solution on Pulau Pari aims to address the limitations in electricity access and dependency on fossil fuel energy sources. This training involves a collaboration between a higher education institution and Karang Taruna, a community organization on Pulau Pari. The objective of the training is to enhance the community's understanding of solar cell usage and management. By applying a method that involves problem identification, preliminary studies, training program planning, development of training materials, training implementation, evaluation, and feedback, the community can improve their understanding of the use and management of solar cells.. The research findings indicate that the use of solar cells improves energy usage efficiency, participants' knowledge and understanding, positive environmental impacts, and energy sustainability. These findings are supported by the nature of solar cell energy conversion, participants' knowledge, trends in renewable energy adoption variables, and comparisons with previous research. This training is expected to provide better understanding, practical guidance, and a positive contribution to improving the quality of life for the community and preserving the environment on Pulau Pari.